PENGARUH BIAYA, WAKTU PENGERJAAN DAN KUALITAS PRODUK MELALUI KEPUTUSAN PEMBUATAN SUKU CADANG DAN DAMPAKNYA PADA KINERJA DI DEPARTEMENT WORKSHOP AND CONSTRUCTION PT SEMEN BATURAJA (PERSERO) Tbk. - Sri Wandoyo; Neny Rostiati; Omar Hendro (Integritas Jurnal Manajemen Profesional (IJMPRO), 2020)
The purpose of the research is specifically to obtain the influence of Cost, Production Time and Product Quality trough decision for making spare part influence on performance Departement Workshop and Constuction PT. Semen Baturaja (Persero) Tbk. The research method uses descriptive survey, field data collection using questionnaire and observation techniques. This research uses a mix method in the form of quantitative research that is equipped with qualitative data. Samples taken as many as 100 people who are echelon I, II, III, and IV employees. Data processing using SERVO Analysis tools and SPSS software version. Testing data with realibility test using cronbach’s alpha, get value of cost efficiency = 0.965 > 0.60, production time = 0.974 > 0.60, quality product = 0.971 > 0.60, corporate performance = 0.970 > 0.60, decision for making spare part = 0.946 > 0.60. that the variable of cost efficeiency, production time, quality product, corporate performance, decision for making spare part on performance Departement Workshop and Constuction PT. Semen Baturaja (Persero) Tbk. Cost have positive and significant effect towards decision for making sparepart in Departement Workshop and Construction PT. Semen Baturaja (Persero) Tbk as big as 20.4%, Production Time have positive and significant effect towards decision for making sparepart in Departement Workshop and Construction PT. Semen Baturaja (Persero) Tbk as big as 38.2%, Product Quality have positive and significant effect towards decision for making sparepart in Departement Workshop and Construction PT. Semen Baturaja (Persero) Tbk as big as 39.7%.